Pendampingan Menulis Puisi Metode Think-Pair-Share pada Siswa sebagai Penguatan Pendidikan Karakter - Ulwatunnisa, Marwah; Arifin, Syaiful; Indrahastuti, Tri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The aim of this community service activity is to provide education and learning to the students of SMAN 5 Samarinda, in order to enhance their writing skills and character education using the Think-Pair-Share method. This activity is particularly beneficial in developing potential and interest in literary works. The implementation of this PKM involves three stages: preparation, activity execution, and report preparation. During the execution phase, participants will be provided with materials on poetry, the building blocks or structure of poetry, and poetry writing techniques. The Think-Pair-Share method will then be applied as follows: Think; participants discuss the task in groups, Pair; participants work in groups to complete the task, and Share; participants present their group's writing results and listen to the opinions of other groups. Finally, participants will practice independently in groups under guidance to produce literary works, specifically poetry.